Survival Outcome in Patients with Cardiomyopathy Detected by Gated SPECT Myocardial Perfusion Imaging (Bangladesh Journal of Nuclear Medicine, 2019)
Objective: Quantitative assessment of LV dysfunction and viability through gated SPECT myocardial perfusion imaging (GSMPI) in addition to being diagnostic surrogate of cardiomyopathy (CM), are being increasingly reported as a predictor of adverse outcome in CM. This study was conducted to investigate the survival outcome in patients diagnosed with CM by GSMPI at National Institute of Nuclear Medicine & Allied Sciences (NINMAS).Patients and methods:  Patients who underwent Tc-99m Sestamibi GSMPI at NINMAS from January 2007 to December 2009 and were diagnosed with CM were retrospectively included in the study. The GSMPI parameters of diagnosis of CM were a left ventricular ejection fraction (EF) at rest of less than 40% with a corresponding end diastolic left ventricular volume (EDV) of more than 130 ml. Telephonic interviews of those patients were conducted in the year 2015 to obtain their clinical follow up data.Results: Fifty two patients (M/F=50/2) were diagnosed to have CM over a period of three years. Follow up data of 19 (M/F=18/1) patients with mean age 52.9±7.4 (38-65), EF 29.1±6.6 (18-39), EDV 211±45.4 (135-320) were available. Nine (47.4%) patients were alive at the time of follow up and 10 (52.6%) patients were found to be deceased. Thus, in this patient group one and five year survival was estimated to be 68 and 47%. Comparison of means of pretest probability score, GSMPI parameters of LV function and viability revealed no difference (p > 0.05) between survivors and non-survivors. Test of equality of survival distributions for management strategies revealed no difference either (Log Rank significance, p > 0.05).Conclusions: Five year survival in this study group diagnosed with CM by GSMPI was 47% where pretest probability score, GSMPI parameters and management strategies were not associated with difference of survival.Bangladesh J. Nuclear Med. 21(2): 81-86, July 2018